Effect of a Quality Improvement Bundle to Standardize the Use of Intravenous Fluids for Hospitalized Pediatric Patients: A Stepped-Wedge, Cluster Randomized Clinical Trial - Rooholamini, Sahar N; Jennings, Brittany; Zhou, Chuan; Kaiser, Sunitha V; Garber, Matthew D; Tchou, Michael J; Ralston, Shawn L (JAMA pediatrics, 2022)
Given that hypotonic maintenance intravenous fluids (IVF) may cause hospital-acquired harm, in November 2018, the American Academy of Pediatrics released a clinical practice guideline recommending the use of isotonic IVF for patients aged 28 days to 18 years without contraindications. No recommendations were made regarding laboratory monitoring; however, unnecessary laboratory tests may contribute to health care waste and harm patients. To examine the effect of a quality improvement intervention bundle on (1) increasing the mean proportion of hours per hospital day with exclusive isotonic IVF use to at least 80% and (2) decreasing the mean proportion of hospital days with laboratory tests obtained. This stepped-wedge, cluster randomized clinical trial (Standardization of Fluids in Inpatient Settings [SOFI]) was sponsored by a national quality improvement collaborative and was conducted across 106 US pediatric hospitals. The SOFI intervention period was from September 2019 to March 2020. Hospital sites were exposed to educational materials, a clinical algorithm and order set for IVF use, electronic medical record interventions to reduce laboratory testing, and "harms of overtesting" cards. Primary outcomes were mean proportion of hours per hospital day receiving exclusive isotonic IVF and mean proportion of hospital days with laboratory test values obtained. Secondary measures included total IVF duration per hospital day, daily patient weight measurement while receiving IVF, serum sodium testing, and adverse events. Baseline data were collected for 2 months; intervention period data, 7 months. Outcomes were analyzed using linear mixed-effects regression models. A total of 106 hospitals were randomly assigned to 1 of 3 intervention start dates (wedges), and 100 hospitals (94%) completed the study. In total, 5215 hospitalizations were reviewed before the intervention, and 6724 hospitalizations were reviewed after the intervention. Prior to interventions, the mean (SD) proportion of hours per day with exclusive isotonic IVF use was 88.5% (31.7%). Interventions led to an absolute increase of 5.4% (95% CI, 3.9%-6.9%) above baseline in exclusive isotonic IVF use but did not change the proportion of hospital days during which a laboratory test value was obtained (estimated difference, 0.1%; 95% CI, -1.5% to 1.7%; P = .90), IVF use duration (estimated difference, -1.2%; 95% CI, -2.9% to 0.4%), serum sodium testing, or adverse events. There was an absolute increase of 4.4% (95% CI, 2.6%-6.2%) in the mean proportion of hospital days with a patient weight measurement while receiving IVF. In this stepped-wedge, cluster randomized clinical trial, an intervention bundle significantly improved the use of isotonic maintenance IVF without a concomitant increase in adverse events or electrolyte testing. Further work is required to deimplement laboratory testing. ClinicalTrials.gov Identifier: NCT03924674.